Teaching English to the Elementary School Students in Kutoarjo District - Kuwat Kuwat; Imam Ghozali (Universitas Sarjanawiyata Tamansiswa, 2018)
The process of teaching English as a foreign language involves the use of target language as a means of providing language exposure to the students. The apropriate amount and quality of the use of target language affect the quality of the instruction. The present paper reports an effort of describing degree of the use of English by teachers in teaching process, techniques teachers use and problems the teachers usually face of their teaching activity. This research belongs to a case study involving four English teachers in Kutoarjo District. Two teachers were selected from advanced schools with complete facilities, while the other two from rural schools with mediocre facilities. The result shows that degree of the use of English by teachers varies. T1 uses 25% English in teaching, T2 20%, T3 35% and T4 40% in their instruction. Further, it is also revealed that teachers use various techniques in their teaching process. They also face some problems. For example T1’s students have poor vocabulary mastery which can affect the teaching learning process. T2 often feels difficult to master the classroom atmosphere. Some T2’s students have unstable motivation to learn English. The pronunciation of T4 find students’ poor pronunciation becomes a problem.